2011
DOI: 10.1136/gut.2010.226407
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of portal hypertension and the hyperdynamic circulatory syndrome in cirrhotic rats by neuropeptide Y via pronounced splanchnic vasoaction

Abstract: Background Splanchnic vasodilation triggers the development of the hyperdynamic circulatory syndrome in portal hypertension. Neuropeptide Y (NPY), a sympathetic co-transmitter of norepinephrine, improves contractility in mesenteric arteries of pre-hepatic portal hypertensive rats. Therefore, we investigated the effect of NPY on mesenteric arterial contractility in vitro and in vivo in cirrhotic ascitic rats, as well as the vasoactive pathways involved. Methods All experiments were performed in CCl 4 -induced c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 50 publications
(39 reference statements)
1
46
0
Order By: Relevance
“…We did not find any SNPs reaching genome-wide significance with DBP or with either SBP-or DBP-measured postpuberty, but when we reduced our statistical significance threshold to P≤5×10 −3 , there were several additional variants in gene clusters relating to SBP or DBP across the 3 epochs. At this more liberal P value threshold, we found some evidence of overlap in novel SNPs across childhood/adolescent age epochs within our study and some overlap with those that have been found by previous GWAS to be associated with adult BP.ITGA11 was genome-wide associated with SBP during the prepubertal epoch and has been shown to be associated with hypertrophic cardiomyopathy 43 and coronary artery disease. 44 An SNP in close proximity to the SMARCA and VLDLR genes (rs872256) was genome-wide associated with SBP during the pubertal epoch.…”
supporting
confidence: 47%
“…We did not find any SNPs reaching genome-wide significance with DBP or with either SBP-or DBP-measured postpuberty, but when we reduced our statistical significance threshold to P≤5×10 −3 , there were several additional variants in gene clusters relating to SBP or DBP across the 3 epochs. At this more liberal P value threshold, we found some evidence of overlap in novel SNPs across childhood/adolescent age epochs within our study and some overlap with those that have been found by previous GWAS to be associated with adult BP.ITGA11 was genome-wide associated with SBP during the prepubertal epoch and has been shown to be associated with hypertrophic cardiomyopathy 43 and coronary artery disease. 44 An SNP in close proximity to the SMARCA and VLDLR genes (rs872256) was genome-wide associated with SBP during the pubertal epoch.…”
supporting
confidence: 47%
“…This substantiates the clinical significance of the observed lack of splanchnic NPY release. Furthermore, NPY deficiency could explain our previous findings, namely why the following effects of external NPY were more markedly pronounced in portal hypertension: NPY (i) inhibited eNOS-and nNOS-mediated NO production and its vasodilating effect [16,38], (ii) enhanced vasoconstrictive Rho-A kinase expression and activity [38], and (iii) reduced portal pressure and portal blood flow [38]. Here exogenous NPY not only corrected mesenteric PNS-induced pressure response in portal hypertension, but markedly slowed the desensitization process, restoring vascular sensitivity to PNS-induced endogenous NA.…”
Section: Discussionmentioning
confidence: 82%
“…NPY-induced potentiation of a 1 -adrenergic vasoconstriction via postsynaptic Y 1 receptors is well known [13,14,38]. Besides, prejunctional NPY effects have been studied in healthy rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased orexigenic response to NPY has been shown in cholestatic rats (29). Amelioration of portal hypertension and the hyperdynamic circulatory syndrome has been observed in cirrhotic rats by NPY via pronounced splanchnic vasoaction (25).…”
Section: Discussionmentioning
confidence: 99%